The Influence of Corporate Social Responsibility to Stock Return - Haryanto, Hery; Kelvin, Kelvin; Hesniati, Hesniati (Jurnal Maksipreneur, 2025)
The research investigates the impact of Corporate Social Responsibility (CSR) on stock returns in the mining sector of Indonesia. The study examines data from financial reports and annual reports of 37 Indonesian companies listed on the stock exchange between 2017 and 2021. The research measures stock return using various factors, including corporate social responsibility, firm age, firm size, return on equity (ROE), and return on assets (ROA). The results reveal that there is a significant positive relationship between ROA and stock return. However, firm age shows a significant negative relationship with stock return, whereas firm size, ROE, and CSR do not have a significant effect. The research findings contribute to the existing literature by suggesting that in Indonesia, investors do not consider CSR as a key factor when making investment decisions since they are not particularly interested in the CSR activities undertaken by companies.